Impact of structure and organization of smallholders on agricultural carbon emissions - Yi, Yujie; Gu, Chuan (Frontiers in Environmental Science, 2022)
Achieving carbon neutrality in agricultural production is a common challenge faced by agricultural development around the world. If China’s agriculture sector intends to achieve the “dual carbon” goal, the focus should be on the agricultural carbon emission of smallholder farmers and their organized production. This study discusses the impact of smallholder structure and organized production on carbon emission, and the interaction mechanism. To describe the causal relationship and mechanism, the structural degree of smallholder farmers and the total carbon emission in the regions were measured, the provincial panel data were constructed, and then the fixed-effects model and intermediary mechanism test were used for empirical analysis. The results show that in the current stage of agricultural development, the high proportion of smallholders in the region will lead to more agricultural carbon emissions. Although organized production services can reduce carbon emissions, the structure of smallholders will inhibit the scale of the organization, thus hindering carbon emission reduction. It is stated that inhibition is the intermediary path for carbon emissions. This study suggests that the government should improve policies to guide smallholders to operate on an appropriate scale, strengthen policies to encourage smallholders to use socialized agricultural production services, and support smallholders in developing highly valuable ecological agriculture.